Characteristics of SAPHO Syndrome: Clinical Analysis of 19 Cases - Wenting SUN, Qiuai KOU (Zhongguo quanke yixue, 2022)
Background SAPHO syndrome is a rare chronic inflammatory disease of unknown causes with various clinical manifestations, which involves bone joint and skin tissue, and has no specific diagnostic indicators and uniform treatment strategy. Objective To analyze the clinical characteristics of 19 cases of SAPHO syndrome, increasing clinicians' recognition of the disease. Methods A retrospective analysis was performed on clinical characteristics 19 cases of SAPHO syndrome recruited from Rheumatology Clinic, Xiyuan Hospital of China Academy of Chinese Medical Sciences from October 2013 to December 2021, including the first symptoms, bone joint and skin involvement, laboratory and imaging findings, comorbidities prevalence, surgical history, medication, follow-up, and misdiagnosis prevalence. Results There were 17 female cases and two male cases, with an average age of (43±12) years and an average duration of 1 year. The first symptom was bone joint pain (n=14) or dermatological manifestations (n=5) . Sixteen patients (84.2%) had bone joint and skin involvement, and the other three (15.8%) had only bone joint involvement. Anterior chest wall was the most commonly involved site, followed by the spine, peripheral joints, and sacroiliac joints. Palmoplantar pustulosis was the most common manifestation of skin involvement (16 cases, 84.2%) , and among these cases, two also had psoriasis-like lesions on the lower extremities and seven also had damaged fingernails of both hands. Eighteen cases had whole-body bone scintigraphy, and were detected with an average number of sites of bone joint involvement of (3±1) . Misdiagnosis occurred in 10 cases (52.6%) , and the average diagnostic delay for them was (3±5) years. Palmoplantar pustulosis was found in all 6 cases (31.6%) with tonsillitis, and the symptoms were improved with no recurrence within one year in two out of three cases undergoing tonsillectomy. Conclusion As a rare disease mainly involving bone joint and the skin, SAPHO syndrome has a high misdiagnosis rate. The recognition of the common involved parts of the disease and whole-body bone scintigraphy and other imaging examinations are helpful to make a proper diagnosis. Tonsillitis may be related to the development of the disease.